Organic gold paste, gold film and application thereof
By using specific organosilicon compounds and organosilicon compounds in the organic gold conductor slurry, nanosilicon dioxide is formed to be embedded between the gold particles, which solves the problem of poor wear resistance of the gold film and improves the good conductivity and wear resistance of the gold film.
Patent Information
- Application Number
- CN202411652865.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
AI Technical Summary
The gold film formed by sintering of the existing organic gold conductor slurry has poor wear resistance, and it is difficult to increase the purity of the gold film by adding other substances to improve wear resistance.
Using specific organosilicon compounds combined with organogold compounds, nanosilicon dioxide is thermally decomposed during the sintering process, and uniformly embedded between gold particles, improving the wear and scratch resistance of the gold film.
It achieves good conductivity, surface flatness and excellent wear and scratch resistance of the gold film, and meets the production needs of electronic components.
Smart Images

Figure BDA0005141407020000041 
Figure BDA0005141407020000121 
Figure BDA0005141407020000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive materials containing metals or alloys, and in particular to an organic gold paste, a gold film and applications thereof. Background Art
[0002] Gold-based conductor pastes are widely used in the production of electronic components such as hybrid integrated circuits, microwave hybrid integrated circuits, multi-chip modules, thermal print heads, etc. due to their high electrical conductivity, stable performance, easy hot-press welding, and strong bonding strength with substrates. Among them, organic gold conductor paste has the characteristics of low cost and low sintering temperature, and is often used as a conductor electrode in thermal printing modules. Organic gold conductor paste mainly includes gold compounds, other metal compounds and organic carriers. However, the wear resistance of the gold film formed by sintering the organic gold conductor paste is poor; moreover, in order to ensure the yield of the gold film bonding, the purity of the gold film usually needs to be higher than 98%, and it is difficult to improve the wear resistance by adding other substances. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an organic gold paste, a gold film and applications thereof.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] In a first aspect, the present invention provides an organic gold paste comprising an organic gold compound, an organic silicon compound and an organic carrier; the temperature at which the organic silicon compound is thermally decomposed to form nano-silicon dioxide is ≤700°C.
[0006] The present invention combines a specific organic silicon compound with an organic gold compound, so that in the process of sintering the organic gold paste to form a gold film, before the gold particles generated by the decomposition of the organic gold compound are sintered and melted, the organic silicon compound can be thermally decomposed to form nano-silicon dioxide and evenly embedded between the gold particles, thereby making the gold film formed by sintering have good conductivity, good surface flatness and excellent wear and scratch resistance.
[0007] Moreover, the study found that when the temperature of thermal decomposition of organosilicon compounds to form nano-silicon dioxide is higher than 700°C, the formed nano-silicon dioxide cannot be evenly dispersed between the gold particles, and it is difficult to effectively improve the wear and scratch resistance of the gold film. The temperature at which organosilicon compounds thermally decompose to form nano-silicon dioxide refers to the complete decomposition temperature of the organosilicon compounds, which can be obtained by testing the thermogravimetric curve using a thermogravimetric analyzer.
[0008] As a preferred embodiment of the organic gold paste of the present invention, the mass ratio of the organic silicon compound to the organic gold compound is (0.002-0.02):1, and is further preferably (0.003-0.01):1. Specifically, it can be any one of 0.002:1, 0.004:1, 0.006:1, 0.008:1, 0.01:1, 0.012:1, 0.014:1, 0.016:1, 0.018:1, and 0.02:1, or a range value between any two of them.
[0009] The study found that the mass ratio of organosilicon compounds to organogold compounds affects the inlay effect of nano-silica formed by the thermal decomposition of organosilicon compounds between gold particles. When the mass ratio of the two is within the above range, it can not only effectively avoid the agglomeration and precipitation of nano-silica to ensure that the gold film has a good surface flatness, but also enable the nano-silica particles to fully fill and evenly disperse in the gaps between the gold particles, thereby enhancing the reinforcing effect of the nano-silica particles on the structure, thereby significantly improving the wear and scratch resistance of the gold film.
[0010] As a preferred embodiment of the organic gold paste of the present invention, the weight average molecular weight of the organosilicon compound is ≤5500, preferably 200-5500, further preferably 500-5000, and specifically can be any one of 200, 400, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500 or a range value between any two of them.
[0011] The study found that the weight-average molecular weight of the organosilicon compound will affect the precipitation effect of nano-silica during the sintering process of the organic gold paste to form a gold film. The organosilicon compound with the above-mentioned weight-average molecular weight can better ensure the precipitation amount of nano-silica, thereby significantly improving the wear and scratch resistance of the gold film.
[0012] As a preferred embodiment of the organic gold paste of the present invention, the organic silicon compound contains active functional groups, and the active functional groups include at least one of vinyl, hydroxyl, carboxyl, and epoxy groups. Studies have found that active functional groups represented by vinyl, hydroxyl, carboxyl, or epoxy groups are conducive to promoting the breakage and recombination of silicon-oxygen chains and silicon-carbon chains to better form nano-silicon dioxide, thereby promoting the improvement of the wear resistance and scratch resistance of the gold film.
[0013] As a preferred embodiment of the organic gold paste of the present invention, the mass content of the active functional groups in the organic silicon compound is 1% to 20% and the mass content of the hydrophilic functional groups (hydroxyl and carboxyl) is ≤5%. Optionally, the mass content of the active functional groups in the organic silicon compound can be 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, and the mass content of the hydrophilic functional groups can be 1%, 2%, 3%, 4%, 5%.
[0014] The mass content of active functional groups in organosilicon compounds = relative molecular mass of active functional groups × number of active functional groups / molecular weight of organosilicon compounds. Specifically, a proper amount of organic gold slurry can be taken, eluted multiple times with solvents such as acetone and toluene, and dried, the obtained organic components are separated by thin layer chromatography or column chromatography, and analyzed by infrared spectroscopy, nuclear magnetic resonance (H spectrum and Si spectrum) and gas chromatography-mass spectrometry, and the types of organosilicon, molecular weight and functional groups of organosilicon and other characteristics can be analyzed.
[0015] Studies have found that active functional groups in organosilicon compounds can promote the formation of nano-silica. When the mass content of hydrophilic functional groups (hydroxyl, carboxyl) is ≤5%, it is more conducive to regulating the particle size and uniformity of nano-silica, thereby better improving the surface smoothness of the gold film.
[0016] As a preferred embodiment of the organic gold paste of the present invention, it also includes other organic metal compounds, and the other organic metal compounds include at least one of organic rhodium compounds, organic lead compounds and organic bismuth compounds; the organic carrier includes an organic binder and an organic solvent.
[0017] As a preferred embodiment of the organic gold paste of the present invention, it includes the following components in parts by weight: 40-70 parts of organic gold compound, 0.1-1 part of organic silicon compound, 0.5-5 parts of organic rhodium compound, 0.5-5 parts of organic lead compound, 0.5-5 parts of organic bismuth compound, 10-40 parts of organic binder, and 1-10 parts of organic solvent.
[0018] Optionally, the weight proportion of the organic gold compound in the organic gold paste can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts; the weight proportion of the organic silicon compound can be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts; the weight proportion of the organic rhodium compound can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts; the weight proportion of the organic lead compound can be 0 .5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, and 5 parts; the weight parts of the organic bismuth compound can be specifically 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, and 5 parts; the weight parts of the organic binder can be specifically 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, and 40 parts; the weight parts of the organic solvent can be specifically 2 parts, 4 parts, 6 parts, 8 parts, and 10 parts.
[0019] As a preferred embodiment of the organic gold paste of the present invention, at least one of the following conditions is met:
[0020] a. The organic gold compound is at least one of sulfide balsam gold, mercaptan gold, rosin acid gold, neodecanoate gold, and isooctanoate gold;
[0021] b. The organosilicon compound includes at least one of an organosilicon resin, polysiloxane, an organosilicon rubber, and a silane coupling agent;
[0022] Optionally, the chemical formula of the polysiloxane is as shown in formula (1):
[0023]
[0024] In formula (1), Me is a methyl group, R1 is an aliphatic hydrocarbon side chain containing any one of vinyl, hydroxyl, epoxy and carboxyl functional groups, and m and n are the number of two different chain segments. Optionally, the polysiloxane may be at least one of polydimethyl-methylvinylsiloxane, polydimethyl-methylhydroxysiloxane, polydimethyl-methylglycidylpolysiloxane and polydimethyl-methylhydroxypropylpolysiloxane.
[0025] c. The organic lead compound, organic bismuth compound or organic rhodium compound is present in the form of at least one of abietic acid salt, octanoic acid salt, cyclopentaneic acid salt and acetylacetonate salt;
[0026] d. The organic binder includes at least one of ethyl cellulose, epoxy resin, polyurethane resin, polyester resin, acrylic resin, alkyd resin, and phenolic resin; preferably, the molecular weight of the organic binder is 20,000 to 50,000;
[0027] e. The organic solvent includes at least one of terpineol, turpentine, toluene, butanone and petroleum ether.
[0028] In a second aspect, the present invention provides a gold film, which is made by sintering the above-mentioned organic gold paste.
[0029] Optionally, the gold film can be prepared by the following preparation method: coating the organic gold paste onto a substrate, allowing the wet film to stand to fully level, and then sintering the leveled wet film to form a gold film.
[0030] In the above preparation method, the coating method can be any one of screen printing, dipping and spraying; the standing temperature is 20-70°C and the time is 0.5-2 minutes; the sintering temperature is 800-900°C and the time is 10-15 minutes.
[0031] In a third aspect, the present invention provides the use of the above-mentioned organic gold paste or gold film in the preparation of electronic components.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The present invention combines a specific organic silicon compound with an organic gold compound, so that in the process of sintering the organic gold paste to form a gold film, before the gold particles generated by the decomposition of the organic gold compound are sintered and melted, the organic silicon compound can thermally decompose to form nano-silicon dioxide and be evenly embedded between the gold particles, thereby making the gold film formed by sintering have good conductivity and surface flatness, and excellent wear resistance and scratch resistance. DETAILED DESCRIPTION
[0034] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0035] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.
[0036] 1. Raw materials and reagents
[0037] Ethyl cellulose (Dow STD-4), epoxy resin (Dow DER331), polyurethane resin (pandex T-8190N), polyester resin (GK-680), acrylic resin (B-890), alkyd resin (389-9), and phenolic resin (Pryofen J325) are all commercially available.
[0038] 2. Examples 1 to 26 and Comparative Examples 1 to 3
[0039] Example 1
[0040] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0041] 50 parts of organic gold compound (sulfur balsam gold);
[0042] 0.5 parts of an organosilicon compound (polydimethyl-methylvinylsiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 500°C, the weight average molecular weight is 1000, the mass content of active functional groups is 10%, and the mass content of hydrophilic functional groups is 0%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.01:1;
[0043] 5 parts of an organic lead compound (lead octoate), 5 parts of an organic bismuth compound (bismuth octoate), 2.75 parts of an organic rhodium compound (rhodium octoate);
[0044] 30 parts of organic binder (ethyl cellulose), 7 parts of organic solvent (toluene).
[0045] Example 2
[0046] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 1, except that:
[0047] The weight portion of the organosilicon compound is 0.375 parts, that is, the mass ratio of the organosilicon compound to the organogold compound is 0.0075:1.
[0048] Example 3
[0049] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 1, except that:
[0050] The weight portion of the organosilicon compound is 0.25 parts, that is, the mass ratio of the organosilicon compound to the organogold compound is 0.005:1.
[0051] Example 4
[0052] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 1, except that:
[0053] The weight portion of the organosilicon compound is 0.15 parts, that is, the mass ratio of the organosilicon compound to the organogold compound is 0.003:1.
[0054] Example 5
[0055] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 1, except that:
[0056] The weight portion of the organosilicon compound is 1 part, that is, the mass ratio of the organosilicon compound to the organogold compound is 0.02:1.
[0057] Example 6
[0058] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 1, except that:
[0059] The weight portion of the organosilicon compound is 0.1 part, that is, the mass ratio of the organosilicon compound to the organogold compound is 0.002:1.
[0060] Example 7
[0061] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0062] The organic silicon compound is polydimethyl-methylvinylsiloxane, the temperature at which the polydimethyl-methylvinylsiloxane is thermally decomposed to form nano-silicon dioxide is 400° C., and the weight average molecular weight is 500.
[0063] Example 8
[0064] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0065] The organosilicon compound is polydimethyl-methylvinylsiloxane, the temperature at which the polydimethyl-methylvinylsiloxane is thermally decomposed to form nano-silica is 525° C., and the weight average molecular weight is 1500.
[0066] Example 9
[0067] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0068] The organic silicon compound is polydimethyl-methylvinylsiloxane, the temperature at which the polydimethyl-methylvinylsiloxane is thermally decomposed to form nano-silica is 588° C., and the weight average molecular weight is 3,000.
[0069] Example 10
[0070] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0071] The organosilicon compound is polydimethyl-methylvinylsiloxane, the temperature at which the polydimethyl-methylvinylsiloxane is thermally decomposed to form nano-silica is 649° C., and the weight average molecular weight is 5,000.
[0072] Embodiment 11
[0073] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0074] The organic silicon compound is tetraethoxysilane, the temperature at which tetraethoxysilane is thermally decomposed to form nano-silicon dioxide is 400° C., and the weight average molecular weight is 208.
[0075] Example 12
[0076] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0077] The organosilicon compound is polydimethyl-methylvinylsiloxane, the temperature at which the polydimethyl-methylvinylsiloxane is thermally decomposed to form nano-silica is 696° C., and the weight average molecular weight is 5,500.
[0078] Embodiment 13
[0079] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0080] The organic silicon compound is polydimethyl-methylvinylsiloxane, and the mass content of active functional groups in the polydimethyl-methylvinylsiloxane is 7%.
[0081] Embodiment 14
[0082] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0083] The organic silicon compound is polydimethyl-methylvinylsiloxane, and the mass content of active functional groups in the polydimethyl-methylvinylsiloxane is 4%.
[0084] Embodiment 15
[0085] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0086] The organic silicon compound is polydimethyl-methylvinylsiloxane, and the mass content of active functional groups in the polydimethyl-methylvinylsiloxane is 1%.
[0087] Example 16
[0088] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0089] The organic silicon compound is polydimethylsiloxane, and the mass content of active functional groups in the polydimethylsiloxane is 0%.
[0090] Embodiment 17
[0091] This embodiment provides an organic gold paste, which is basically the same as that of embodiment 3, except that:
[0092] The organic silicon compound is polydimethyl-methylhydroxysiloxane, in which the mass content of active functional groups is 10% and the mass content of hydrophilic functional groups is 10%.
[0093] Embodiment 18
[0094] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0095] 65 parts of an organic gold compound (gold thiolate);
[0096] 0.65 parts of an organosilicon compound (polydimethyl-methylglycidylpolysiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 379° C., the weight average molecular weight is 500, the mass content of active functional groups is 20%, and the mass content of hydrophilic functional groups is 0%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.01:1;
[0097] 4.8 parts of an organic lead compound (lead octoate), 4.75 parts of an organic bismuth compound (bismuth octoate), 4.8 parts of an organic rhodium compound (rhodium octoate);
[0098] 10 parts of organic binder (bisphenol A epoxy resin), 10 parts of organic solvent (pinene alcohol).
[0099] Embodiment 19
[0100] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0101] 40 parts of an organic gold compound (gold thiolate);
[0102] 0.25 parts of an organosilicon compound (polydimethyl-methylglycidylpolysiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 554°C, the weight average molecular weight is 1700, the mass content of active functional groups is 13%, and the mass content of hydrophilic functional groups is 0%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.00625:1;
[0103] 3 parts of an organic lead compound (lead naphthenate), 3.25 parts of an organic bismuth compound (bismuth naphthenate), and 3.5 parts of an organic rhodium compound (rhodium naphthenate);
[0104] 40 parts of organic binder (bisphenol A epoxy resin), 10 parts of organic solvent (pinene alcohol).
[0105] Embodiment 20
[0106] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0107] 55 parts of an organic gold compound (gold thiolate);
[0108] 0.55 parts of an organosilicon compound (polydimethyl-methylcarboxypropyl polysiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 602°C, the weight average molecular weight is 3500, the mass content of active functional groups is 2%, and the mass content of hydrophilic functional groups is 2%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.01:1;
[0109] 3 parts of an organic lead compound (lead naphthenate), 3.9 parts of an organic bismuth compound (bismuth naphthenate), and 3.55 parts of an organic rhodium compound (rhodium naphthenate);
[0110] 25 parts of organic binder (phenolic resin), 9 parts of organic solvent (pinene alcohol).
[0111] Embodiment 21
[0112] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0113] 60 parts of an organic gold compound (gold rosinate);
[0114] 0.45 parts of an organosilicon compound (polydimethyl-methylcarboxypropyl polysiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 562° C., the weight average molecular weight is 2500, the mass content of active functional groups is 1%, and the mass content of hydrophilic functional groups is 1%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.0075:1;
[0115] 2.45 parts of an organic lead compound (lead naphthenate), 3.6 parts of an organic bismuth compound (bismuth naphthenate), and 2.5 parts of an organic rhodium compound (rhodium naphthenate);
[0116] 25 parts of organic binder (phenolic resin), 6 parts of organic solvent (turpentine).
[0117] Embodiment 22
[0118] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0119] 60 parts of an organic gold compound (gold rosinate);
[0120] 0.6 parts of an organosilicon compound (silane coupling agent KH-858: the temperature of thermal decomposition to form nano-silicon dioxide is 250°C, the weight average molecular weight is 538, the mass content of active functional groups is 0%, and the mass content of hydrophilic functional groups is 0%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.01:1;
[0121] 2.7 parts of an organic lead compound (lead acetylacetonate), 2.2 parts of an organic bismuth compound (bismuth acetylacetonate), and 3.5 parts of an organic rhodium compound (rhodium acetylacetonate);
[0122] 28 parts of organic binder (alkyd resin), 3 parts of organic solvent (turpentine).
[0123] Embodiment 23
[0124] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0125] 50 parts of an organic gold compound (gold neodecanoate);
[0126] 0.4 parts of an organosilicon compound (silane coupling agent KH-858: the temperature of thermal decomposition to form nano-silicon dioxide is 250°C, the weight average molecular weight is 538, the mass content of active functional groups is 0%, and the mass content of hydrophilic functional groups is 0%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.008:1;
[0127] 3 parts of an organic lead compound (lead acetylacetonate), 3.1 parts of an organic bismuth compound (bismuth acetylacetonate), 3.5 parts of an organic rhodium compound (rhodium acetylacetonate);
[0128] 30 parts of organic binder (acrylic resin), 10 parts of organic solvent (methyl ethyl ketone).
[0129] Embodiment 24
[0130] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0131] 65 parts of an organic gold compound (gold neodecanoate);
[0132] 0.26 parts of an organosilicon compound (polydimethyl-methylhydroxypropyl polysiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 548°C, the weight average molecular weight is 2000, the mass content of active functional groups is 2%, and the mass content of hydrophilic functional groups is 2%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.004:1;
[0133] 4.2 parts of an organic lead compound (lead acetylacetonate), 4.34 parts of an organic bismuth compound (bismuth acetylacetonate), 4.2 parts of an organic rhodium compound (rhodium acetylacetonate);
[0134] 21 parts of organic binder (acrylic resin), 1 part of organic solvent (methyl ethyl ketone).
[0135] Embodiment 25
[0136] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0137] 70 parts of an organic gold compound (gold 2-ethylhexanoate);
[0138] 0.56 parts of an organosilicon compound (polydimethyl-methylhydroxypropyl polysiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 628°C, the weight average molecular weight is 4500, the mass content of active functional groups is 1%, and the mass content of hydrophilic functional groups is 1%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.008:1;
[0139] 1.7 parts of an organic lead compound (lead rosinate), 1.24 parts of an organic bismuth compound (bismuth rosinate), and 1.5 parts of an organic rhodium compound (rhodium rosinate);
[0140] 20 parts of organic binder (polyurethane resin), 5 parts of organic solvent (petroleum ether).
[0141] Embodiment 26
[0142] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0143] 70 parts of an organic gold compound (gold 2-ethylhexanoate);
[0144] 0.28 parts of an organosilicon compound (polydimethyl-methylglycidylpolysiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 550°C, the weight average molecular weight is 1000, the mass content of active functional groups is 17%, and the mass content of hydrophilic functional groups is 0%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.004:1;
[0145] 0.5 parts of an organic lead compound (lead rosinate), 0.72 parts of an organic bismuth compound (bismuth rosinate), and 0.5 parts of an organic rhodium compound (rhodium rosinate);
[0146] 24 parts of organic binder (polyurethane resin), 4 parts of organic solvent (petroleum ether).
[0147] Comparative Example 1
[0148] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0149] 50 parts of organic gold compound (sulfur balsam gold);
[0150] 0 parts of organosilicon compounds;
[0151] 5 parts of an organic lead compound (lead octoate), 5 parts of an organic bismuth compound (bismuth octoate), 2.5 parts of an organic rhodium compound (rhodium octoate);
[0152] 30 parts of organic binder (ethyl cellulose), 7 parts of organic solvent (toluene).
[0153] Comparative Example 2
[0154] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0155] 50 parts of organic gold compound (sulfur balsam gold);
[0156] 0.25 parts of an organosilicon compound (polydimethyl-methylphenylsiloxane: the temperature of thermal decomposition to form nano-silicon dioxide is 750°C, the weight average molecular weight is 1000, the mass content of active functional groups is 10%, and the mass content of hydrophilic functional groups is 0%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.005:1;
[0157] 5 parts of an organic lead compound (lead octoate), 5 parts of an organic bismuth compound (bismuth octoate), 2.5 parts of an organic rhodium compound (rhodium octoate);
[0158] 30 parts of organic binder (ethyl cellulose), 7 parts of organic solvent (toluene).
[0159] Comparative Example 3
[0160] This embodiment provides an organic gold paste, which includes the following components in parts by weight:
[0161] 50 parts of organic gold compound (sulfur balsam gold);
[0162] 0.25 parts of an organosilicon compound (polydimethyl-methylvinylsiloxane: the temperature of thermal decomposition to form nano-silica is 710°C, the weight average molecular weight is 6500, the mass content of active functional groups is 10%, and the mass content of hydrophilic functional groups is 0%), that is, the mass ratio of the organosilicon compound to the organogold compound is 0.005:1;
[0163] 5 parts of an organic lead compound (lead octoate), 5 parts of an organic bismuth compound (bismuth octoate), 2.75 parts of an organic rhodium compound (rhodium octoate);
[0164] 30 parts of organic binder (ethyl cellulose), 7 parts of organic solvent (toluene).
[0165] The method for preparing the organic gold paste in the above-mentioned Examples 1 to 26 and Comparative Examples 1 to 3 comprises the following steps:
[0166] The organic gold paste is prepared by uniformly mixing components of an organic gold compound, an organic silicon compound, an organic rhodium compound, an organic lead compound, an organic bismuth compound and an organic carrier, and then rolling the mixture with a three-roller machine.
[0167] 3. Performance testing
[0168] The organic gold pastes in Examples 1 to 26 and Comparative Examples 1 to 3 were respectively coated on the substrate by screen printing, and allowed to stand at 70°C for 5 minutes to allow the wet film to fully level. The leveled wet film was then sintered in a mesh belt furnace at 850°C for 15 minutes to form a gold film, and then the gold film was subjected to the following tests.
[0169] 1) Volume resistivity test: Use a four-probe square resistance meter to test the square resistance, and then calculate the volume resistivity in combination with the thickness of the gold film to characterize the conductivity. Place the gold film sample on the measuring table, and press the four probes of the instrument vertically down to contact the sample surface to obtain the square resistance value. Calculate the volume resistivity based on the square resistance value combined with the thickness of the gold film, volume resistivity = square resistance / gold film thickness. The volume resistivity value should not exceed 50mΩ / μm.
[0170] 2) Wear and scratch resistance: Use a pencil hardness tester to test the wear and scratch resistance. Place the sintered gold film at the tip of the pencil hardness tester, push the instrument to move, and observe whether there is light transmission at the scratched part of the gold film under a metallographic microscope; then, gradually increase the weight of the pencil hardness tester tip until light transmission occurs at the scratched part of the gold film; when light transmission occurs at the scratched part of the gold film, the tip weight is ≥600g, indicating that the gold film has good wear and scratch resistance.
[0171] 3) Surface flatness: Use a laser scanner to measure the surface roughness Ra. The smaller the roughness Ra, the better the flatness of the gold film.
[0172] Table 1 Performance of organic gold paste in Examples 1 to 26 and Comparative Examples 1 to 3
[0173]
[0174]
[0175] According to the data in Table 1, the volume resistivity of the gold film made by using the organic gold paste in Examples 1 to 26 is all <38.5 mΩ / μm, reaching 34 to 38.3 mΩ / μm; the pen tip weight is all ≥600 g, reaching 600 to 695 g); the roughness Ra≤0.08, reaching 0.02 to 0.08 μm, indicating that the organic gold paste of the present invention can make the gold film maintain good conductivity while having good surface flatness and excellent wear and scratch resistance.
[0176] At the same time, according to Comparative Example 1, it can be seen that the pen tip weight of the gold film made of organic gold paste without adding organic silicon compounds is only 450g, that is, the wear and scratch resistance of the gold film is poor, indicating that the organic silicon compound plays a key role in improving the wear and scratch resistance of the gold film; in addition, according to Comparative Examples 2 and 3, when the temperature of the added organic silicon compound thermally decomposes to form nano-silicon dioxide is too high, it makes it difficult to form nano-silicon dioxide before the gold particles are sintered and melted, which effectively improves the wear and scratch resistance of the gold film and cannot meet the application requirements of the gold film.
[0177] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An organic gold paste, characterized in that: The invention comprises an organic gold compound, an organic silicon compound and an organic carrier; the temperature at which the organic silicon compound is thermally decomposed to form nano silicon dioxide is ≤700°C.
2. The organic gold paste according to claim 1, characterized in that: The mass ratio of the organic silicon compound to the organic gold compound is (0.002-0.02):
1.
3. The organic gold paste according to claim 1, characterized in that: The weight average molecular weight of the organosilicon compound is ≤5500.
4. The organic gold paste according to claim 1, characterized in that: The organic silicon compound contains active functional groups, and the active functional groups include at least one of vinyl, hydroxyl, carboxyl and epoxy groups.
5. The organic gold paste according to claim 4, characterized in that: The mass content of active functional groups in the organic silicon compound is 1% to 20%, and the mass content of hydrophilic functional groups is ≤5%.
6. The organic gold paste according to claim 1, characterized in that: Also included are other organometallic compounds, the other organometallic compounds comprising at least one of an organorhodium compound, an organolead compound and an organobismuth compound; The organic vehicle includes an organic binder and an organic solvent.
7. The organic gold paste according to claim 6, characterized in that: The composition comprises the following components in parts by weight: 40-70 parts of organic gold compound, 0.1-1 parts of organic silicon compound, 0.5-5 parts of organic rhodium compound, 0.5-5 parts of organic lead compound, 0.5-5 parts of organic bismuth compound, 10-40 parts of organic binder and 1-10 parts of organic solvent.
8. The organic gold paste according to claim 6, characterized in that: Satisfy at least one of the following: a. The organic gold compound is at least one of sulfide balsam gold, mercaptan gold, rosin acid gold, neodecanoate gold, and isooctanoate gold; b. The organosilicon compound includes at least one of an organosilicon resin, polysiloxane, an organosilicon rubber, and a silane coupling agent; c. The organic lead compound, organic bismuth compound or organic rhodium compound is present in the form of at least one of abietic acid salt, octanoic acid salt, cyclopentaneic acid salt and acetylacetonate salt; d. The organic binder includes at least one of ethyl cellulose, epoxy resin, polyurethane resin, polyester resin, acrylic resin, alkyd resin, and phenolic resin; e. The organic solvent includes at least one of terpineol, turpentine, toluene, butanone and petroleum ether.
9. A gold film, characterized in that: It is made by sintering the organic gold paste described in any one of claims 1 to 8.
10. Use of the organic gold paste according to any one of claims 1 to 8 or the gold film according to claim 9 in the preparation of electronic components.